A national census of those attending UK accident and emergency departments with asthma. The UK National Asthma Task Force. Issue 1 (January 1997) - Partridge, M R; Latouche, D; Trako, E; Thurston, J G
Abstract : OBJECTIVE: To obtain a representative national picture of the type of people with asthma attending accident and emergency (A&E) departments in the UK, the reasons why they attend, and to determine the proportion admitted to hospital. DESIGN: A national census involving questionnaires. SETTING: 100 A&E departments throughout the UK. SUBJECTS: All those with asthma attending because of asthma during a one week period in September 1994. RESULTS: Details were obtained about 1292 attendances. About half of all attendances were by adults and half by children, and 87.8% were previously diagnosed asthmatics; 18.8% of adult attenders were unemployed. Perceived severity of asthma was the reason for attendance in 65.5%, but 11.5% reported non-availability, or perceived non-availability, of the general practitioner (GP) as the reason for attending. One fifth of adults had been kept awake by their asthma for over three nights before attendance. 425 of the 1292 attenders (32.9%) had been admitted to hospital in the previous 12 months and 316 (24.5%) had attended the A&E department in the previous three months. Only 24.6% of attenders had had contact with their general practitioner in the previous 24 h. 61.6% of under-5 attenders (n = 341) were admitted to hospital; the figures for those aged 5-15 and 15+ years and above were 265 (41.4%) and 665 (38.7%). CONCLUSIONS: Many people with asthma attend A&E departments without first having seen their GP. In many adult cases the asthma, while severe, is not acute, but a high proportion of both adults and children are admitted to hospital. Many of these attendances and admissions are repeat attendances. To enhance the quality of care provided to those with asthma may require easier access to primary care, enhanced patient education, or enhanced health professional education. Further study is needed of a variety of potential interventions.